Como resolver a equação: 1/5(6x-1)-(3x-1)=1+5/2(3x+8).
Soluções para a tarefa
Respondido por
3
Oi :)
![\frac{1}{5} (6x-1)-(3x-1)=1+ \frac{5}{2} (3x+8) \\ \\ \frac{6x-1}{5}-3x+1=1+ \frac{15x+40}{2} \\ \\ \frac{6x-1}{5}-3x= \frac{15x+40}{2} \\ \\ \frac{2(6x-1)-10(3x)=5(15x+40)}{10} \\ \\ 12x-2-30x=75x+200 \\ \\ -18x-75x=200+2 \\ \\ -93x=202 \\ \\93x=-202 \\ \\x= -\frac{202}{93} \frac{1}{5} (6x-1)-(3x-1)=1+ \frac{5}{2} (3x+8) \\ \\ \frac{6x-1}{5}-3x+1=1+ \frac{15x+40}{2} \\ \\ \frac{6x-1}{5}-3x= \frac{15x+40}{2} \\ \\ \frac{2(6x-1)-10(3x)=5(15x+40)}{10} \\ \\ 12x-2-30x=75x+200 \\ \\ -18x-75x=200+2 \\ \\ -93x=202 \\ \\93x=-202 \\ \\x= -\frac{202}{93}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B5%7D+%286x-1%29-%283x-1%29%3D1%2B+%5Cfrac%7B5%7D%7B2%7D+%283x%2B8%29+%5C%5C++%5C%5C++%5Cfrac%7B6x-1%7D%7B5%7D-3x%2B1%3D1%2B+%5Cfrac%7B15x%2B40%7D%7B2%7D++%5C%5C++%5C%5C+++%5Cfrac%7B6x-1%7D%7B5%7D-3x%3D+%5Cfrac%7B15x%2B40%7D%7B2%7D++%5C%5C++%5C%5C++%5Cfrac%7B2%286x-1%29-10%283x%29%3D5%2815x%2B40%29%7D%7B10%7D++%5C%5C++%5C%5C+12x-2-30x%3D75x%2B200+%5C%5C++%5C%5C+-18x-75x%3D200%2B2+%5C%5C++%5C%5C+-93x%3D202+%5C%5C++%5C%5C93x%3D-202+%5C%5C%C2%A0%5C%5Cx%3D+-%5Cfrac%7B202%7D%7B93%7D+)
betaniasouza22:
Valeu!
Respondido por
0
1(6x-1)-(3x-1)=1+ 5(3x+8) mmc = 10
5 2
2(6x-1) - 10(3x - 1) = 10 + 25(3x + 8)
12x - 2 - 30x + 10 = 10 + 75x + 200
12x - 30x - 75x = 200 + 10 + 2 - 10
- 93x = 202(-1)
93x = - 202
x = - 202
93
5 2
2(6x-1) - 10(3x - 1) = 10 + 25(3x + 8)
12x - 2 - 30x + 10 = 10 + 75x + 200
12x - 30x - 75x = 200 + 10 + 2 - 10
- 93x = 202(-1)
93x = - 202
x = - 202
93
Perguntas interessantes
Matemática,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Informática,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás